Promoted room-temperature LPG gas sensor activities of graphene oxide@Fe2O3 composite sensor over individuals. (19th September 2018) - Ghule, Balaji G; Shaikh, Shoyebmohamad F; Shinde, Nanasaheb M; Sangale, Sushil S; Shinde, Pritamkumar V; Mane, Rajaram S
Abstract: Graphene oxide (GO), iron oxide (Fe2 O3 ) and GO@Fe2 O3 composite sensors, obtained at 0.1, 1.0, 10 wt% concentrations of GO in Fe2 O3, of different structures, morphologies, porosities, surface areas, and charge transfer resistances, etc, have been synthesized via a simple, economic, solid-state synthesis strategy and envisaged as an efficient room-temperature (27 °C) liquefied petroleum gas (LPG) sensors. Spherical Fe2 O3 and island-type GO have contributed their individual the sensing signatures in GO@Fe2 O3 composite sensors. With GO loading in various wt%, intensity of the reflection peaks of Fe2 O3 in x-ray diffraction patterns decreases, indicating dominance of an amorphous contribution in GO@Fe2 O3 . The electrical conductivity of the composite sensor decreases due to generation of various charge transport channels with increase of GO wt% concentration. However, for concentrations more than 1 wt% of the GO both pore-size and surface area of GO@Fe2 O3 decreases. The 1 wt% GO@Fe2 O3 composite sensor reveals ∼35% room-temperature (27 °C) LPG sensitivity @100 ppm level over pristine GO (∼15%) and Fe2 O3 (∼25%), and also other GO@Fe2 O3 composite sensors (20%–30%), attributed to their increased specific surface area and reduced charge transfer resistance, which, in general, have more surface active surface sites for adsorbing LPG molecules than those of individual and other low-surface area sensors.